Stress, mental symptoms and well-being in students: a gender analysis - del Pino, María-José; Matud, M. Pilar (Frontiers in Psychology, 2024)
IntroductionStress is a major problem among students, threatening their health and well-being. The aim of the research is to analyze the sources of stress in students and to investigate whether there are gender differences and differences between university and non-university students in stress, coping styles, mental symptoms and well-being. A second aim is to know the relevance of age, education, stress, coping styles, self-esteem and social support on mental symptoms, psychological well-being and life satisfaction of boys and girls.MethodsThe study was cross-sectional. The sample consisted of 1,426 students between the ages of 16 and 26.Results and discussionThe results of the ANOVAs showed that although there were some gender differences, being a university student or not explained more variance than gender. University students had more chronic stress than non-university students. However, they were more satisfied with their studies, had healthier coping styles, fewer mental symptoms, and greater well-being. For both genders, the main predictor of more mental symptoms was a higher emotional coping style. This was followed by lower self-esteem, a higher number of stressful life events, and higher chronic stress. Higher study dissatisfaction was associated with lower psychological well-being and lower life satisfaction. Higher chronic stress was associated with lower life satisfaction. It is concluded that stress and coping styles are relevant to students’ mental health. The results of this study are relevant to the design of policies, strategies, and programs to improve students’ mental health and well-being.